Rates of Return to Education: The View of Students in Switzerland - Stefan C. Wolter; André Zbinden (Institute for the Study of Labor (IZA), 2001)
Wage expectations are important determinants for individual schooling decisions. However, research on individual expectations of students is scarce. The paper presents the Swiss results of a survey that was conducted in 10 European countries. Its main findings are that point estimates of wages after graduation are close to actual wages, whereas the expectations of the wage gain in the first ten years of professional experience exceed the actual wage gains significantly. While most of the deviation of individual expectations from actual wages can not be explained, we find that rates of return to education that are calculated on the base of individual wage and cost expectations as well as individual time preferences can be explained partially by the seniority of students, the self-perception of their academic performance and their subjective job perspectives. The high degree of unexplained heterogeneity in individual expectations and the differences between groups of students show the necessity to analyse the question further with bigger and more representative samples.
Keywords: C81; J31; I20; J24; 330; Rates of return to education; wages; expectations; Bildungsertrag; Lohn; Studierende; Erwartungstheorie; Schätzung; Schweiz